If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 6x + -2x = -10 Combine like terms: 6x + -2x = 4x 6 + 4x = -10 Solving 6 + 4x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4x = -10 + -6 Combine like terms: 6 + -6 = 0 0 + 4x = -10 + -6 4x = -10 + -6 Combine like terms: -10 + -6 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| 25t^2+45t=0 | | 5log(5x-10)=15 | | 3ln(2X)=27 | | 10(3x+12)+13x-14= | | 3h=-18 | | 48-5x=18 | | 3+4x+5x=48 | | 8(x-9)=15 | | -3+-b=1 | | 2x-(24/x)-8=0 | | x+2y-3=xy | | 15x^2-27y^2=12 | | 4(3x+7)=10 | | 7y+4(y-5)=4(y+1)-2 | | -7r=14 | | 3(5x+9)=37+19 | | x^2-27y^2=12 | | A^2+12a=-32 | | -3=p/6-6 | | 8a+-3=5 | | 3(2x+3)=2x-7 | | 7(4x-6)-7=28x-49 | | ln(x+2)+ln(x+4)=2 | | 3x+5x-4=4 | | 4(5x+6)+2(8-x)= | | 8y+3y+18=2y | | P^2=35+2p | | 106.2+4x=180 | | 11y-6=2y | | -.5*32x^2+24x+50=58 | | -3+5y=17 | | 28.5+.75x=36.75 |